Cognitive Dysfunction in Schizophrenia - Susana Anggar Kusuma; Yunias Setiawati (Faculty of Medicine, Universitas Airlangga, 2020)
Schizophrenia is a mental disorder which includes: positive symptoms, negative symptoms, cognitive symptoms, affective symptoms and aggressive symptoms. Cognitive disorder is the most severe disorder compared to other symptoms of schizophrenia because it can interfere with daily functions, including memory function, attention function, problem solving function, speech function and social skills.